Social Studies Learning Strategies in Developing Social Knowledge and Skills in Junior High Schools - Irwansyah Abbas (Yayasan Insan Mulia Bima, 2023)
The main competence of social studies learning is inseparable from the mastery of social knowledge and social skills in preparing students to become good citizens of society and the nation. This research aims to describe the strategies for developing social knowledge and social skills in social studies learning at SMPN 1 Monta. The research method used is qualitative descriptive. Data were obtained from interviews and observations at SMPN 1 Monta with both teachers and students. The data analysis involved a stepwise data verification process and used three approaches to qualitative data analysis: Data Display, Data Interpretation, and Drawing Conclusions. The results of this research show that teachers use strategies to transform social knowledge correlated with daily life content in the surrounding environment, making the material understanding directly meaningful to students. Meanwhile, to enhance students' social skills, guidance and reinforcement of local social values and national character values are conducted, enabling students to internalize these values and become moral benchmarks for behavior in the school and community where they reside.